2019
DOI: 10.1149/2.0481903jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Composite Cathode Using Bimodal Sized Electrolyte for All-Solid-State Batteries

Abstract: To enhance the packing density of composite cathode for all-solid-state lithium-ion batteries, the effect of a bimodal sized solid electrolyte was studied. The composite cathode, which is fabricated using the powder compression method, consisted of the cathode active material, a conductive agent, and the solid electrolyte. However, the composite cathode construction had voids. The voids in the composite cathode were restricted to ionic conduction between the cathode active materials and the solid electrolytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
(32 reference statements)
0
49
0
Order By: Relevance
“…Despite being a mere proof of concept in which many parameters of importance have not been optimized (particles sizes, electrode composition, mixing technique, etc.) 36,37 , the results are truly promising. The addition of LTFS had a clear positive impact in the battery performance mainly ascribed to a lower CM/SE interface resistance.…”
Section: Figure 7 Herementioning
confidence: 90%
“…Despite being a mere proof of concept in which many parameters of importance have not been optimized (particles sizes, electrode composition, mixing technique, etc.) 36,37 , the results are truly promising. The addition of LTFS had a clear positive impact in the battery performance mainly ascribed to a lower CM/SE interface resistance.…”
Section: Figure 7 Herementioning
confidence: 90%
“…By mixing large and small particles with optimized ratios, a better energy density could be realized [18]. Park et al [19] have reported that optimized bimodal-sized active materials can minimize voids and maximize the packing density. A bimodal structure could also improve electrochemical performance due to a large contact area between large particles and small particles [19].…”
Section: Resultsmentioning
confidence: 99%
“…Park et al [19] have reported that optimized bimodal-sized active materials can minimize voids and maximize the packing density. A bimodal structure could also improve electrochemical performance due to a large contact area between large particles and small particles [19]. The particle size and the shape of the graphite powder are shown in Figure 1c,d.…”
Section: Resultsmentioning
confidence: 99%
“…[149,182] However, bimodal-sized SE powders are more desirable than those with a single particle size distribution from the view of the suppression of voids. [183] The composite cathode consisting of bimodal sized SE powders possesses the highest packing density (3.14 g cm −3 ) and the largest AM-SE contact area (62.04%) compared to those of electrodes consisting of only coarse or fine SE particles. [183] Similarly, Peng et al, studied the effect of NCA particle size on the physical contact and interfacial chemical stability between AM particles and sulfide SEs, and found that the physical contacts and interfacial compatibility were improved after the NCA was treated with ball-milling followed by post-annealing.…”
Section: Am and Se Particle Sizementioning
confidence: 97%
“…[183] The composite cathode consisting of bimodal sized SE powders possesses the highest packing density (3.14 g cm −3 ) and the largest AM-SE contact area (62.04%) compared to those of electrodes consisting of only coarse or fine SE particles. [183] Similarly, Peng et al, studied the effect of NCA particle size on the physical contact and interfacial chemical stability between AM particles and sulfide SEs, and found that the physical contacts and interfacial compatibility were improved after the NCA was treated with ball-milling followed by post-annealing. [184] Next, Strauss et al studied the relationships between the secondary particle size of the cathode AM and electrochemical performance in ASSLBs comprising NCM622, β-Li 3 PS 4 , and In anode via electrochemical tests and X-ray diffraction experiments combined with Rietveld refinement analysis.…”
Section: Am and Se Particle Sizementioning
confidence: 97%